Obesity and elevated blood pressure among adolescents in Lagos, Nigeria: a cross-sectional study - Oduwole Abiola A; Ladapo Taiwo A; Fajolu Iretiola B; Ekure Ekanem N; Adeniyi Olufunmilayo F (BMC Public Health, 2012)
Abstract Background Childhood obesity and associated hypertension are major public health concerns globally. This study aimed to determine the prevalence of obesity and the associated risk of high blood pressure among Nigerian adolescents. Methods A cross-sectional school-based study of 885 apparently healthy adolescents was performed. Weight, height and blood pressure (BP) were measured using standard methods. Body mass index (BMI) was calculated and categorized by age, sex and percentile. Obesity and overweight were defined as: ≥ 95th and 85th to < 95th percentiles, respectively, for age, sex and height. Subjects were sub-categorized into age 10–13 years (A) and 14–17 years (B). The odds ratio for pre-hypertensive and hypertensive range BP by age and BMI were generated. Significance was set at P < 0.05. Results The prevalence of overweight and obesity were 13.8% and 9.4%, respectively. The prevalence of hypertensive range systolic BP in obese versus normal BMI females was 16% versus 23% (p=0.00) and 12.1% versus 6.4% (p=0.27) in males. The prevalence of hypertensive range diastolic BP in obese versus normal BMI females was 12% versus 1.4% (p=0.00) and 15.2% versus 3.5% (p=0.01) in males. BMI in group B was significantly associated with pre-hypertensive and hypertensive range systolic BP in overweight (P = 0.01, P = 0.002) and obese subjects (P = 0.00, P = 0.00) and with hypertensive range diastolic BP (P = 0.00) only in obese subjects. The only significant association in group A was between obesity and pre-hypertensive range diastolic BP (P = 0.00). Conclusion The prevalence of hypertensive range BP among obese Nigerian adolescents was high. Screening for childhood obesity and hypertension, and long-term follow-up of obese adolescents into adulthood are recommended.